Downdraft impacts on tropical convection - Thayer-Calder, Katherine, author; Randall, David, advisor; Johnson, Richard, committee member; Maloney, Eric, committee member; Strout, Michelle, committee member (Colorado State University. Libraries, 2013)
Downdrafts are an integral part of the convective cycle, and have been observed and documented for more than a hundred years. But many questions still surround convective downdrafts and their most difficult to observe properties. These questions have made the parameterization of convective downdrafts in global climate models (GCMs) very difficult. Designers of parameterizations have resorted to a wide range of assumptions and unverified hypotheses in their models of convective downdrafts. In the last ten years, computing resources have advanced to a point where large domain, high resolution cloud resolving models (CRMs) can easily be run for long simulations. This study uses several simulations with 1 km horizontal resolution from the System for Atmospheric Modeling (SAM) v6.8.2 to examine convective downdrafts. We look at Radiative-Convective Equilibrium (RCE), a 21 day case from TOGA-COARE, Weak Temperature Gradient (WTG) simulations with varied shear profiles, and Lagrangian Parcel data to consider many difficult to observe properties of downdrafts. We consider a variety of assumptions and questions that arise in the development of convective parameterizations. Our results show that downdrafts are an important mass flux in all simulations, and that cold pools organize convective systems and enhance updraft Convective Available Potential Energy (CAPE). We examine the ability for downdrafts to help couple deep convection to high relative-humidity regions in the tropics, and find that entrainment is likely a more important process in this relationship. We discuss the impact of downdrafts in maintaining boundary layer quasi-equilibrium, and find that, in our simulations, environmental entrainment has a larger impact on low-level most static energy. Finally, we show results from Lagrangian parcel data that illuminate our downdrafts as existing in an unsaturated state, with increasing buoyancy as they descend. We show that many of our downdrafts have positive buoyancy perturbations, suggesting the presence of warm downdrafts and under-shooting bottoms in heavily precipitating tropical systems.
Keywords: climate; cloud; convection; downdraft; model; parameterization